Massively parallel sequencing analysis of benign melanocytic naevi. Issue 1 (24th May 2019) - Lozada, John R; Geyer, Felipe C; Selenica, Pier; Brown, David; Alemar, Barbara; Merghoub, Taha; Berger, Michael F; Busam, Klaus J; Halpern, Allan C; Weigelt, Britta; Reis‐Filho, Jorge S; Hollmann, Travis J
Abstract : Aims: Melanocytic naevi are benign lesions of the skin or mucosa that may constitute non‐obligate precursors of malignant melanoma, particularly when they show lentiginous and dysplastic features. The aim of this study was to investigate the repertoire of somatic genetic alterations in melanocytic naevi. Methods and results: DNA extracted from 12 melanocytic naevi and DNA from matching normal tissue were separately microdissected and subjected to targeted massively parallel sequencing of ≥300 cancer genes. A median of 5.5 (range 1–12) non‐synonymous somatic mutations were detected, with 10 cases harbouring mutually exclusive BRAF V600E (6/12) or NRAS (4/12) clonal hotspot mutations. One of the two cases lacking BRAF and NRAS mutations was a dysplastic naevus harbouring an HRAS Q61L hotspot mutation. Analysis of the laser‐capture microdissected components of a naevus synchronously diagnosed with in‐situ and invasive malignant melanoma revealed a truncal, clonal BRAF V600E mutation, and the acquisition of a CDKN2A homozygous deletion in the invasive component, in conjunction with additional clonal mutations affecting NF2, FAT4 and KDR in both in‐situ and invasive malignant components. Conclusion: Melanocytic naevi harbour recurrent BRAF V600E or NRAS hotspot mutations with low mutational burdens. Our findings also show that progression from naevi to malignant melanoma may be driven by the acquisition of additional genetic alterations, including CDKN2A homozygous deletions.